2008
DOI: 10.1097/mcg.0b013e318050074f
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Hepatocellular Carcinoma in Chronic Hepatitis C Patients by Transient Elastography

Abstract: Liver stiffness measured by transient elastography is useful in demarcating chronic hepatitis C patients at a high risk for HCC, who require frequent check-up by imaging examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 24 publications
1
58
2
Order By: Relevance
“…Even in so-called ''cirrhotic'' patients, the possibility of HCC presence was elevated slightly when the liver stiffness was less than 24 kPa. However, once the stiffness exceeded 24 kPa, this possibility rose steeply, which was comparable with the report on patients with HCV by Masuzaki et al [13]. He pointed out that the possibility of HCC presence in HCV-related cirrhosis patients increases from 1.3-to 5-fold when the liver stiffness is higher than 25 kPa.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Even in so-called ''cirrhotic'' patients, the possibility of HCC presence was elevated slightly when the liver stiffness was less than 24 kPa. However, once the stiffness exceeded 24 kPa, this possibility rose steeply, which was comparable with the report on patients with HCV by Masuzaki et al [13]. He pointed out that the possibility of HCC presence in HCV-related cirrhosis patients increases from 1.3-to 5-fold when the liver stiffness is higher than 25 kPa.…”
Section: Discussionsupporting
confidence: 74%
“…Liver stiffness measurement (LSM) by TE is a rapid, non-invasive, reproducible and operator-friendly method, which has been reported as accurately representing the state of liver fibrosis [8][9][10][11][12]. It was recently proposed to assess the risk of HCC development in patients with chronic HCV infection by TE [13]. The aim of this study was to assess the relationship between liver stiffness and the risk of HCC presence in patients with chronic hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of chronicity after acute HCV infection is above 80% (Alter et al, 1992;Seeff, 1995), and some patients will ultimately develop liver cirrhosis and hepatocellular carcinoma (Gane, 2008;Kwon and Bae, 2008;Masuzaki et al, 2008). Due to the high mutation rate of the HCV genome, effective vaccines have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In shear wave elastography, the measurement of liver stiffness (LS) is affected greatly by the severity of inflammation, jaundice and congestion besides liver fibrosis [12,13,14,15,16]. In addition, LS is highly correlated with the risk of liver cancer in chronic hepatitis patients [17,18,19]. Although a study using shear wave elastography with the employment of FibroScan reported that LS was improved by interferon (IFN) therapy [20], the association between strain elastography and antiviral therapy has not been clarified.…”
Section: Introductionmentioning
confidence: 99%